The Influence of Board Gender Diversity on Financial Performance of Manufacturing Companies Listed on the IDX - Arifa Cantika Rosliputri; Robith Hudaya (Citakonsultindo, 2024)
This study aims to ascertain how gender diversity affects the financial performance of manufacturing businesses listed on the IDX by looking at the composition of direction and commissioner boards. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. This research used a purposive sampling technique and produced a sample of 72 companies. This research uses panel data regression analysis. The program that supports the analysis of this test data is Eviews 12. The results of this research are that the gender diversity of the board of commissioners does not affect the financial performance of manufacturing companies. The gender diversity of the board of directors does not affect the financial performance of manufacturing companies. The independent board of commissioners influences the financial performance of manufacturing companies. The company's size is independent of the financial performance of the manufacturing company.